Locked Knee and Inferior Patellar Dislocation in an Elderly Patient: A Case Report and Review of the Literature - Jeremy Silver; Jared Sain; Michael Simon; Kenneth G. Swan (Journal of Orthopaedic Case Reports)
Introduction: Inferior patellar dislocations in elderly patients are rare and typically occur in the presence of significant patellofemoral arthritis. These dislocations often present as a locked knee, which can be mistaken for other knee pathologies. While treatment has generally involved closed reduction, there is limited literature on recurrence and the role of surgical intervention. Case Report: An 85-year-old female presented with a locked right knee following a fall, unable to bear weight or extend the knee. Radiographs and MRI revealed an inferior patellar dislocation due to a superior patellar osteophyte interacting with a defect in the lateral femoral condyle. Initial closed reduction was successful but followed by a recurrence of the dislocation seven weeks later. Arthroscopic surgery, including debridement of the patellar osteophyte and trochlear osteochondral defect, provided definitive treatment. The patient remained symptom-free at 12 months follow-up with no further dislocations. Conclusion: This case highlights the challenge of managing inferior patellar dislocations in elderly patients, with closed reduction and immobilization often insufficient to prevent recurrence. Arthroscopic surgery should be considered in cases of recurrent dislocation to allow for early mobilization and minimize the risk of further episodes. Level of evidence: Level V Case Report